Impact on the Efficiency and Quality of Life of Medicinal Flora in the Andean Community of Huamachuco, la Libertad, Peru - Martinez-Salinas, J (MS-EDITIONS, 2025)
In the Andean community of Huamachuco, it can be seen that the population resorts to the use of medicinal plants, evidencing positive treatments, due to the presence of metabolites with pharmacological, analgesic and diuretic action. In view of this, the objective of the research was to determine the effectiveness and quality of life of the medicinal flora in Huamachuco. A descriptive study was used, in which 96 semi-structured surveys were applied, with random sampling. 51 species are reported, distributed in 34 families and 49 genera; the families Lamiaceae, Asteraceae and Apiaceae being the most representative. It is concluded that the Andean community of Huamachuco has 51 species of medicinal flora, of which 69% were relieved and 31% were cured by using medicinal plants.